Is there really a renminbi bloc in Asia? - Masahiro Kawai; Victor Pontines (Asian Development Bank Institute (ADBI), 2014)
This paper examines whether the renminbi (RMB) has supplanted the US dollar as the major anchor currency in the currency baskets of East Asian economies. First, we systematically demonstrate that existing techniques to address the problem of severe multicollinearity in estimations of the Frankel-Wei regression model, with the movements in both the RMB and the US dollar included on the right-hand side of the equation, remain limited in providing stable and robust results. Then we propose a simple modification of the Frankel-Wei regression model to estimate the RMB weight in an economy's currency basket. Using this new approach, we find that there is not yet an RMB bloc in East Asia, contrary to claims made by some recent studies. We find that the US dollar continues to be the dominant anchor currency in the region. The RMB has taken on some importance in the currency baskets of many East Asian economies in recent years and this appears to have occurred at the expense of the yen. In short, despite the rising importance of the RMB, it has not eclipsed the US dollar as the dominant anchor currency in East Asia.
Keywords: F15; F31; F36; F41; O24; 330; RMB; renminbi bloc; Frankel–Wei regression model; anchor currency; East Asia; currency baskets